Development of an insect metalloproteinase inhibitor drug carrier system for application in chronic wound infections. (23rd June 2015) - Eisenhardt, Michaela; Dobler, Dorota; Schlupp, Peggy; Schmidts, Thomas; Salzig, Mark; Vilcinskas, Andreas; Salzig, Denise; Czermak, Peter; Keusgen, Michael; Runkel, Frank
Abstract: Objectives: The insect metalloproteinase inhibitor (IMPI) represents the first peptide capable of inhibiting virulence-mediating microbial M4-metalloproteinases and is promising as a therapeutic. The purpose of this study was to develop a suitable drug carrier system for the IMPI drug to enable treatment of chronic wound infections. Specifically, we studied on poloxamer 407 hydrogels, examining the influence of several additives and preservatives on the rheological parameters of the hydrogels, the bioactivity and release of IMPI. Methods: The rheological characterisation of the hydrogel was performed by oscillatory measurements. The bioactivity of IMPI was evaluated in a Casein fluoresence quenching assay. Key findings: In this study, a suitable application form for the dermal treatment of chronic wound infections with IMPI was designed. The influences of poloxamer 407 concentration and various additives on the viscoelastic properties and preservation of a thermosensitive hydrogel were investigated. The incorporation of the precursor drug IMPI–gluthathione-s-transferase (GST) in the hydrogel had no influence on the rheological characteristics and will be released. The bioactivity of IMPI-GST is not influenced by the hydrogel and remains constant over 4 weeks of storage. Conclusions: This study reports the development of a poloxamer hydrogel as a suitable carrier system for the application of IMPI.